Eastern European nomads in Ruthenian chronicles - Vovina, Varvara G. (Balcanica Posnaniensia. Acta et studia, 2007)
Russian chronicles from the 12th–13th centuries provide a wealth of valuable information about how their authors perceived the steppe peoples. The aim of this article is to characterise the chronicle discourse on nomads and to determine its role in shaping the historical and cultural perception of the world by medieval Rus. The research method used was a textual and comparative-historical analysis of chronicle accounts containing information about the Pechenegs, Polovtsians, Bulgars, „Black Klobuks” and Tatars. A comparison of different versions of the texts revealed recurring motifs and ideological assumptions that determined the interpretation of nomadic peoples. The chroniclers paid the most attention to the pagan („unclean”) nature of the steppe peoples. Nomads were most often portrayed as „God's scourge” – a passive instrument of punishment, similar to natural disasters. At the same time, their simplicity and trustfulness were emphasised. The chronicles provide a particularly large amount of information about the Polovtsians, pointing to their combativeness and ancestry, as well as describing the geography of their lands. Attention was paid to the marriages and alliances between the princes of Rus and the Polovtsian elite, which testified to the gradual convergence of the two cultural worlds.